Chemical and pathogen-induced inflammation disrupt the murine intestinal microbiome - Borton, Mikayla A. (Microbiome, 2017)
BACKGROUND: Salmonella is one of the most significant food-borne pathogens to affect humans and agriculture. While it is well documented that Salmonella infection triggers host inflammation, the impacts on the gut environment are largely unknown. A CBA/J mouse model was used to evaluate intestinal responses to Salmonella-induced inflammation. In parallel, we evaluated chemically induced inflammation by dextran sodium sulfate (DSS) and a non-inflammation control. We profiled gut microbial diversity by sequencing 16S ribosomal ribonucleic acid (rRNA) genes from fecal and cecal samples. These data were correlated to the inflammation marker lipocalin-2 and short-chain fatty acid concentrations. RESULTS: We demonstrated that inflammation, chemically or biologically induced, restructures the chemical and microbial environment of the gut over a 16-day period. We observed that the ten mice within the Salmonella treatment group had a variable Salmonella relative abundance, with three high responding mice dominated by >46% Salmonella at later time points and the remaining seven mice denoted as low responders. These low- and high-responding Salmonella groups, along with the chemical DSS treatment, established an inflammation gradient with chemical and low levels of Salmonella having at least 3 log-fold lower lipocalin-2 concentration than the high-responding Salmonella mice. Total short-chain fatty acid and individual butyrate concentrations each negatively correlated with inflammation levels. Microbial communities were also structured along this inflammation gradient. Low levels of inflammation, regardless of chemical or biological induction, enriched for Akkermansia spp. in the Verrucomicrobiaceae and members of the Bacteroidetes family S24-7. Relative to the control or low inflammation groups, high levels of Salmonella drastically decreased the overall microbial diversity, specifically driven by the reduction of Alistipes and Lachnospiraceae in the Bacteroidetes and Firmicutes phyla, respectively. Conversely, members of the Enterobacteriaceae and Lactobacillus were positively correlated to high levels of Salmonella-induced inflammation. CONCLUSIONS: Our results show that enteropathogenic infection and intestinal inflammation are interrelated factors modulating gut homeostasis. These findings may prove informative with regard to prophylactic or therapeutic strategies to prevent disruption of microbial communities, or promote their restoration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40168-017-0264-8) contains supplementary material, which is available to authorized users.